The Implementation of Proyek Penguatan Profil Pelajar Pancasila (P5) with the Theme of Local Wisdom: Students’ Voices - Erma Sujiyani; Handini Siringoringo; Novika Amalia (Poltanesa, 2025)
This study explores how students perceive the implementation of the Pancasila Student Profile Strengthening (P5) program under the theme of Local Wisdom, focusing on both the positive and negative aspects experienced in classroom and project activities. The research used a descriptive qualitative approach involving 30 students from class XI SAINTEK 3 at SMAN 5 Palangka Raya. Data were obtained through questionnaires and interviews to capture a broader and more personal view of their learning experiences. Findings show that 63% of students expressed positive perceptions toward P5, while 37% viewed it less favorably. Students who responded positively described P5 as enjoyable and meaningful, particularly because they could engage directly with cultural practices and teamwork activities that reflected Pancasila values. In contrast, others noted issues such as unclear instructions, lack of organization, and additional material costs, which made the experience less engaging. These differences highlight that while the P5 program supports cultural appreciation and character development, its success depends greatly on facilitation, communication, and resource support. The study suggests that better planning, teacher guidance, and collaboration with local communities are needed to enhance the relevance and sustainability of P5 activities. Overall, the results reflect that the theme of Local Wisdom remains a strong yet challenging approach to cultivating civic and cultural values in the Merdeka Curriculum.